Photoconductor-metadevices: an enabling platform for dual-optical/electrical modulation of terahertz waves. (1st September 2022) - Meng, Lingqiang; Lu, Yelong; Sha, Xin; Zhang, Yu; Liu, Wenquan; Kang, Lei; Konishi, Kuniaki; Werner, Douglas H.; Li, Jia
Abstract: We report a photoconductor-based terahertz metadevice whose transmission characteristics can be comprehensively controlled by a combination of an optical excitation and electrical bias. A metasurface with interdigitated electrodes is proposed to simultaneously support a terahertz resonance and the photoconductive effect, allowing efficient local and global dual-tuning of the carriers in the semiconductor and thus the terahertz wave, based on the simultaneous external optical and electrical stimuli. Experimental results reveal the opposite tuning trend of optical and electrical excitations, leading to the comprehensive transmission modulation of terahertz wave. Our study demonstrates a proof-of-concept device for sophisticated manipulation of terahertz radiation.